2008 8th IEEE International Conference on Automatic Face &Amp; Gesture Recognition 2008
DOI: 10.1109/afgr.2008.4813395
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory factor analysis of gait recognition

Abstract: Many studies have now shown that it is possible to recognize people by the way they walk. As yet there has been little formal study of the effects of covariates on the recognition process. We show how these factors can separately affect the walking pattern. Further we assess the contribution and discriminatory significance of the gait dynamics used for recognition. Based on a covariate-based probe dataset of 440 samples, a high recognition rate of 73.4% is achieved using the KN N classifier. This is to confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…A study [9] has reported a recognition rate of just 3% for the combination of the following covariate factors: clothes, shoes and time. Another study [7] reported a significant drop in performance (87% to 60%) when subjects wore trench coat on top of their normal clothes.…”
Section: B Effect Of Clothesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study [9] has reported a recognition rate of just 3% for the combination of the following covariate factors: clothes, shoes and time. Another study [7] reported a significant drop in performance (87% to 60%) when subjects wore trench coat on top of their normal clothes.…”
Section: B Effect Of Clothesmentioning
confidence: 99%
“…Many studies, such as [6], [7] and [21], do not consider temporal data and focus solely on data acquired on the same day.…”
mentioning
confidence: 99%
“…This extends recent research studies by on covariate analysis [4] and view-point invariant gait recognition [5]. A novel reconstruction method is being employed to rectify and normalize gait features recorded from different view-point into the side-view plane and therefore exploit such data for recognition.…”
Section: Introductionmentioning
confidence: 92%
“…Hence, it is also used for exploratory factor analysis of gait recognition [5]. The recently published Soton Temporal database [23] contains the largest variations, up to 9 months, in elapsed time.…”
Section: Related Workmentioning
confidence: 99%